Native legumes in Minas Gerais State, Brazil - Costa, Nuno Maria de Sousa (International Center for Tropical Agriculture, 1982)
The multiplicity of soils, climates and vegetation types in Minas Gerais State has resulted in a large variation in the genera and species of legumes that occur naturally there. A number of these appear to have forage potential. This paper reports on the occurrence, nodulation and resistance to stress conditions of some naturally occurring species, but emphasizes Stylosanthes spp. In observations of natural settings and field nurseries, six different rooting patterns were found in species of Stylosanthes. Three Stylosanthes species had unusually large nodules, while in S. capitata and S. macrocephala few or no nodules were found under natural field conditions. By contrast S. guianensis var. vulgaris, the new species S. debilis, and S. grandifolia showed good nodulation, even on poor soils. Anthracnose, caused by Colletotrichum gloesporioides was the most serious disease of Stylosanthes species in Minas Gerais, though S. macrocephala and S. capitata appeared less susceptible than other species. Root nematodes and stem borers were not a major problem in Minas Gerais.